Release of enzymes from damaged myocardium - Wong, Peter Chok-Ping (The University of Edinburgh, 1976)
This thesis is concerned with the application and development of serum enzyme tests in the diagnosis of myocardial infarction. Two aspects of the problem have been selected for detailed study: firstly, the measurement of the activity of the MB isoenzyme of creatine kinase and, secondly, the release of mitochondrial enzymes in myocardial infarction. In addition, the biochemical properties of the MB isoenzyme have been compared with those of the MM isoenzyme of creatine kinase in an attempt to provide the basis of a simple test for the measurement of serum levels of the MB isoenzyme.